KAJIAN PENYELIDIKAN DAN PENYIDIKAN TERHADAP PELAKU KEJAHATAN TINDAK PIDANA PENCURIAN DAN PENADAHAN SEPEDA MOTOR ( Studi Kasus Di Polsek Jebres Surakarta ) - SUKOCO, DIRGANTARA PRADIKTA (Dinamika Hukum, 2015)
The purpose of this study to examine the mechanism of inquiry and investigation against the perpetrators of criminal acts of theft and fencing motorcycle happened Jebres police jurisdictions when viewed from the perspective of normative juridical. When viewed from the perspective of normative juridical and whether in the investigation, Article 480 can stand alone without the main perpetrator or perpetrators must coincide with a major theft. Background number of criminal offenses or violations of the laws and acts that deviate from the rules of law, especially the crime of theft, where the offense was committed openly. The type of research used in this research is normative juridical. Secondary data were collected by reviewing the substance of the norms in the Act. The data that has been analyzed using qualitative descriptive method with inductive reasoning methods. Inductive intended for inquiries and investigations against perpetrators of criminal acts of theft of motorcycles and linked to the perspective adopted. This type of research is a normative juridical research. Therefore, in the method of data collection used interviews as a data collection tool that is fundamental to explore primary sources. It is also used to support the data collection tool in the form of documentation. Data collected through interviews and documentation in order to conduct data searches. Based on the results of this study concluded the crime of fencing and the crime of theft is a crime that is different / separate / stand alone set out in clauses differently, the elements of the crime were different so even though the crime of fencing the motorcycle thief unknown file the case can be expressed P-21 for the prosecution related fencing. It is worthy thieves are known to facilitate the examination of evidence in court even though it is not absolute. Keyword: Offence, Theft, Investigation